Electronic Origin and Tailoring of Photovoltaic Effect in BiFeO3 Single Crystals. (7th October 2015) - Yang, Mingmin; Bhatnagar, Akash; Alexe, Marin
Abstract : The sub‐band levels situated around 2.2 eV within the band gap are at the electronic origin of the anomalous photovoltaic effect in BiFeO3 single crystals. The photovoltaic effect can be effectively tailored by controlling the activity of the sub‐band levels via thermal and electrical treatments.